Condiciones psicosociales y económicas laborales de los médicos generales en Medellín, marzo de 1998 (1998)
ABSTRACT: In the present decade the Colombia legislation has suffered transformations that have permitted the change of labor relations materializing the worldwide tendencies of the flexibility of work, and the section of health in general has not been foreign to these changes. Specifically the Law number 100, of 1993, changed the labor relations of doctors upon separating the rendering of health services from the resources of the administration, however, the present study suggested the question in reference to the economic and psychosocial conditions of the general practioners in Medellín. A descrptive study was performed of the make up of the population, that showed how the practice of general medicine in Medellín is consolidated as a practice of a fix salaries or wages, and it is performed less than a liberal practice. According to the results of the study, 60% of the general practioners labored in public institutions, 70% had some link to public institutios and 66% had at least one non-fixed-term contract; no unsatisfaction with their job was found in 53% and 54% said they are always selfdeterminated in taking decisions.